SELECTIVE AREA GROWTH OF III-V-COMPOUND SEMICONDUCTORS BY CHEMICAL BEAM EPITAXY - Davies, G; Skevington, P; French, C; Foord, J (1992)
The reactions of triethylgallium (TEG) on a silicon nitride surface have been investigated to determine the underlying causes for selective area epitaxy. Using the techniques of X-ray photo electron spectroscopy and temperature programmed desorption, TEG is found to weakly adsorb on defect sites at room temperature. Desorption is favoured over further decomposition at higher substrate temperatures. The results are compared with the interaction of TEG on GaAs(100) surface and the implications for the influence of surface arsenic on selective area growth are discussed. © 1992.